Skewed X chromosome inactivation in blood cells of women with scleroderma - (:unkn) unknown (WILEY, 2005)
Objective. Scleroderma (SSc) is an autoimmune disease of unknown etiology. The disease is 3-8 times more frequent in women than in men. The role of X chromosome inactivation (XCI) in the predisposition of women to autoinimunity has been questioned. Until now this has not been illustrated experimentally. This study was undertaken to test the hypothesis that disturbances in XCI mosaicism may be involved in the pathogenesis of the disease in female patients with SSc. Methods. Seventy female SSc patients and 160 female controls were analyzed for the androgen receptor locus by the Hpa II/polymerase chain reaction assay to assess XCI patterns in DNA extracted from peripheral blood cells. Furthermore, skin biopsy samples were obtained from 5 patients whose blood revealed an extremely skewed pattern of XCI, and the analysis repeated. Since microchimerism in SSc was reported, Y chromosome sequences were investigated in all samples. Results. Skewed XCI was observed in DNA from peripheral blood cells in 35 of 55 informative patients (64%), as compared with 10 of 124 informative controls (8%) (P < 0.0001). Extreme skewing was present in 27 of the patient group (49%), as compared with only 3 of the controls (2.4%) (P < 0.0001). However, XCI was random in all skin biopsy samples. The potential contribution of microchimerism to the random XCI pattern is highly unlikely based on the medical histories of the patients. Conclusion. Skewed XCI mosaicism may play a significant role in the pathogenesis of SSc.
Keywords: GENE-ACTION; AUTOIMMUNE; MICROCHIMERISM; ASSOCIATION; SELECTION